Laser dazzler emitting three-colour radiation - Mlynczak, Jaroslaw; Kopczynski, Krzysztof; Włodarski, Maksymilian; Kaliszewski, Miron (Photonics Letters of Poland, 2022)
The article presents a laser dazzle generating three overlapping laser beams of different colours and an analysis of the possibility of dazzling people with this radiation. The analysis took into account the eye’s photopic sensitivity and the additivity of the three radiation beams. Such analysis, to the knowledge of the authors, is presented for the first time. The possibility of dazzling for four different dazzle levels and three levels of ambient luminance was presented. It has been shown that in some conditions it is possible to damage the eye without causing the assumed dazzle effect. Full Text: PDF References Joint Non-Lethal Weapons Program, Non-Lethal Optical Distracters Fact Sheet, (2016). DirectLink https://www.faa.gov/about/initiatives/lasers/laws/ DirectLink N. Raoof, et al., "‘Toy’ laser macular burns in children", Eye 28, 231 (2014). CrossRef D. B. Gosling, J. B. O'Hagan, and F. M. Quhill, "Blue Laser Induced Retinal Injury in a Commercial Pilot at 1300 ft", Aerospace Medicine and Human Performance 87, 69 (2016). CrossRef J. Marshall, J. B. O'Hagan, and J. R. Tyrer, "Eye hazards of laser ‘pointers’ in perspective", Br. J. Ophthalmol. 100, 583 (2016). CrossRef N. Raoof, J. O'Hagan, N. Pawlowska, and F. Quhill, "Toy’ laser macular burns in children: 12-month update", Eye 30, 492 (2016). CrossRef S. Androudi and E. Papageorgiou, "Macular Hole from a Laser Pointer", New England Journal of Medicine 378, 2420 (2018) CrossRef J. E. Neffendorf, G. D. Hildebrand and S. M. Downes, "Handheld laser devices and laser-induced retinopathy (LIR) in children: an overview of the literature", Eye 33, 1203 (2019). CrossRef E. Linton, et al., "Retinal burns from laser pointers: a risk in children with behavioural problems", Eye 33, 492 (2019). CrossRef P. Dockrill, Science alert, (2020). DirectLink IEC 60825-1:2014, Safety of laser products - Part 1: Equipment classification and requirements (International Electrotechnical Commission 2014). DirectLink ANSI Z136.1-2014, American National Standard for Safe Use of Lasers (American National Standards Institute 2014). DirectLink C. A. Williamson and L. N. McLin, "Nominal ocular dazzle distance (NODD)", Appl. Opt. 54, 1564 (2015). CrossRef C. A. Williamson and L. N. McLin, "Determination of a laser eye dazzle safety framework", Journal of Laser Applications 30, 032010 (2018). CrossRef J. Mlynczak, K. Kopczynski, M. Kaliszewski, M. Wlodarski, "Estimation of nominal ocular hazard distance and nominal ocular dazzle distance for multibeam laser radiation", Applied Optics, 60(22), 6414-6421 (2021). CrossRef CVRL Database, CVRL functions, Luminous efficiency functions, 2-deg functions. DirectLink Peter Lennie, Joel Pokorny, and Vivianne C. Smith, "Luminance", Journal of the Optical Society of America A, 10 (6), 1283-1293, (1993) CrossRef H. Cai and T. Chung, "Evaluating discomfort glare from non-uniform electric light sources", Lighting Research & Technology, 45 (3), 267-294 (2012). CrossRef